Morphological and molecular data of two species of the rare genera Thada Thorne, 1941 and Tenunemellus Siddiqi, 1986 (Nematoda: Tylenchidae) from Iran. (2020) - Hosseinvand, M.; Eskandari, A.; Ghaderi, R.; Karegar, A.
Abstract: Thada populus n. sp. was found in the rhizosphere of Populus euphratica in the city of Dezful, south-western Iran. The new species is characterized by its 365–453 μm body length, cuticle with transverse annuli 0.9–1.2 μm wide, lateral fields with four lines, lip region low with one or two annuli, 7.0–8.5 μm wide at base, longitudinal or slightly sigmoid amphidial slit, delicate stylet 8.4–9.8 μm long with posteriorly directed knobs, dorsal pharyngeal gland opening at 1.0–1.5 μm posterior to the stylet knobs, non-muscular and valve-less median bulb, pyriform and offset basal bulb, almost oval spermatheca, posterior position of vulva (V = 75–79%) without lateral membrane, short post-vulval uterine sac and conical tail with finely to broadly rounded terminus. Morphological differences of the new species with those of the type species, Thada striata, are discussed. Molecular phylogenetic studies of the new species using partial sequences of small subunit ribosomal DNA revealed that the new species formed a clade with Malenchus spp., Filenchus facultativus, F. fungivorus and Filenchus sp. in Bayesian inference. Morphological and molecular phylogenetic studies were also performed on Tenunemellus indicus, the second recovered species, the latter analysis using partial sequences of large subunit ribosomal DNA. In the inferred Bayesian tree, T . indicus formed a clade with Labrys fuzhouensis, Lelenchus leptosoma from the Netherlands, Malenchus spp. and Filenchus discrepans .